Comparative Thoughts on Religious Education: The Perspectives of Rabbi Abraham Joshua Heschel, Aminah Wadud, and Reinhold Niebuhr - Hermawan, Ucep; Muhlas, Muhlas (UIN Sunan Gunung Djati Bandung, 2025)
Religious education plays an important role in shaping moral values that are relevant to the challenges of the increasingly complex modern world. This study aims to compare the thoughts of Rabbi Abraham Joshua Heschel, Aminah Wadud, and Reinhold Niebuhr regarding religious education, as well as explore their different perspectives that reflect the richness of their respective theological traditions. Using a qualitative approach and literature study method, this study analyzes the main works of the three figures, including Heschel's Man Is Not Alone, Wadud's Qur'an and Woman, and Niebuhr's The Nature and Destiny of Man, as well as various other relevant sources. The results of the study show that although there are similar views on the importance of religious education that prioritizes morality and social responsibility, these three thinkers have different approaches. Heschel emphasized social morality as an integral part of religious education, Wadud advocated women's empowerment and gender equality, while Niebuhr taught the importance of compromise and adaptation to the complexities of the social world. This research contributes to the development of religious education that is more inclusive and relevant to the social context, as well as enriching interfaith dialogue in a diverse global society.